Problems of the Institutional‑Legal and Organizational Provision of Systemic Innovation Policy: the Case of Ukraine - Inna Koblianska; Larysa Kalachevska (Comparative Economic Research. Central and Eastern Europe, 2019)
The article investigates the "systemic" dimension of the existing institutional-legal and organizational peculiarities of the innovation policy in Ukraine, based on the IS approach, which is seen as one of the main guidelines for the innovation policy formation, and, in particular, underlies the Ukrainian framework as well. The authors found that state strategic documents do not sufficiently reflect the systemic character of the NIS, nor do they place linkages or firms at the core of the national innovation system. Areas are determined where the innovation policy cannot be realized completely because of the current organization of activities and powers of the central executive authorities in this field, specifically: the impact on business, the formation of infrastructure, and the development of linkages. European countries' experience in the field of innovation policy implementation is explored, particularly, the creation and operating of the models of the national innovation agencies as well as the spectrum of their functions. Based on the European experience, it is proposed that a State Agency for Innovation and Development in Ukraine be created that will integrate the functions of regional project funding, provide advice, and realize the basic functions of the innovation intermediary.
Keywords: O32; O38; H11; O52; O57; 330; innovation; innovation system; innovation development institutions; innovation intermediary; innovation policy